A integração entre o planejamento e a execução orçamentária no Instituto Federal da Paraíba - Campus João Pessoa - Santos, Marcos Vicente dos (2022)
The prese n t research had as main objec tive to analyze the integration between the planning and the budget execution at Federal Institute of Paraiba Campus João Pessoa from 2016 to 2019. This study meets its justification in the need of checking if there is integr a tion between th e planning an d the budget execution in the process of execution of the programs and actions planned for João Pessoa Campus. It`s a study of case, with qualiquantitative nature and predominantly descriptive. The scenary was IFPB Campus João P essoa, that, ba sed on the CF 1988, presents its financial sustainability supported primarily on resources transferred by Federal Government. As subjects we had the participation of thirteen managers(11 managers and 2 former managers),who offered to part i cipate in this essay study. The collection of data happened through the appication of semi structured questionaire, containing open and closed questions. Bibliographic research, because books by renowed authors and papers that may be found on sites on in t ernet, which ap proach this t heme. Of Documentary nature, since there was appropriation and consult of several documents, such as budget proposals, management treasure reports, management reports, even if there is limited decentralization concerning the re s ources sent ann ually to the educational institution which is being analyzed, mainly in a scenery of governnamental delay, which impairs the implementation of these policies which integrate constitutional and legal obligations of the Federal Government, we have come to th e conclusion that every public administration which is based on a good planning and defined objectives, tend to carry out a good job for the society within the administrative reality of its sphere of government. In the case of IFPB, there i s transparency in the proces s of elaborating the budget proposal, as well as the documents P rograma de D esenvolvimento I nstitucional are consulted, P rograma de G estão P lano P lurianual , being confirmed that there is integration between the planning and th e budget executi on, according to the analysis and the discussion of the results which refer to the consulted data, although difficulties appear, for it shows that managers worry about the application of the resourses, in favor of a community that needs ass i stance, in rela tion to asset s as well as service.